« Perspectives »Global Regionalization Processes and (Macro)-Regional Integration. In Favor of Generalization in Geography - Nora Mareï; Yann Richard (Belgeo)
Many researchers concur in observing that globalization has abolished neither distance, nor the usefulness of geographical proximity. Spatial constraints continue to shape exchanges, as well as the density and quality of interactions between societies. Even in a globalized world, pervaded with networks that disrupt traditional territorialities, it can be useful and even inevitable to build relationships with one’s neighbors. In this context, the notion of (macro)regional (or multi-state) integration deserves to be exploited. In particular, geographical research has so far eluded this concept, despite this discipline’s recognized expertise on the notions of region, distance, territory and territorial development, which are at the heart of the understanding of regional integration, both theoretically and empirically. This contribution aims to clarify the words, objects and methods of (macro)regional integration from the point of view of geographical semantics, as well as the evolution of theoretical approaches to the notion of region.